Influência da região de extração em propriedades físicas e mecânicas da madeira de Cupiúba (Goupia Glabra Aubl) - Silva, Carlos Eduardo Gomes da (2016)
This research aimed to investigate, with the aid of the Brazilian standard NBR 7190 (1990) Wood Structures Project, of the Kruskal-Wallis analysis of variance (ANOVA), and the regrouping bootstrap technique, the influence of extraction regions Caracaraí, Bonfim and Claudia, in physical and mechanical properties of Cupiúba wood (Goupia Glabra Aubl), and assess the possibility of estimate (linear, exponential, geometric and logarithmic mathematical models) the physical and mechanical properties investigated as a function of density. The results of ANOVA indicated equivalence in 94% of the properties of the regions of Caracaraí and Claudia, and no equivalence in 50% of the properties in the region of Bonfim, even after extrapolated by the bootstrap technique, the non-equivalence was still 44%, whereas the results obtained from the regression model implied a possibility of an estimate of the physical and mechanical properties of Cupiúba wood due to its apparent density.